1996
DOI: 10.1016/0168-6496(96)00025-6
|View full text |Cite
|
Sign up to set email alerts
|

Short exposure to acetylene to distinguish between nitrifier and denitrifier nitrous oxide production in soil and sediment samples

Abstract: The contribution of nitrifiers and denitrifiers to the nitrous oxide production in slurries of calcareous silt loam and river bank sediment at different oxygen concentrations was determined using acetylene as nitrification inhibitor. The addition of 10 Pa acetylene resulted in inhibition of nitrous oxide production at oxic conditions, but strongly enhanced the nitrous oxide production at oxygen-poor and anoxic conditions. Inhibition of nitrification by short exposure (1 to 24 h) to high concentrations of acety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(59 citation statements)
references
References 11 publications
3
56
0
Order By: Relevance
“…Similar observations of other soils have been made where a Ͻ1-to 8-day delay occurred before significant NO 2 Ϫ or NO 3 Ϫ accumulation after acetylene exposure (8,11,34). Extended delays before NO 2 Ϫ or NO 3 Ϫ accumulation could indicate that the forest soil-borne NH 3 oxidizers are sufficiently depleted of energy reserves to hinder the rapid de novo protein synthesis of AMO.…”
Section: Discussionsupporting
confidence: 64%
“…Similar observations of other soils have been made where a Ͻ1-to 8-day delay occurred before significant NO 2 Ϫ or NO 3 Ϫ accumulation after acetylene exposure (8,11,34). Extended delays before NO 2 Ϫ or NO 3 Ϫ accumulation could indicate that the forest soil-borne NH 3 oxidizers are sufficiently depleted of energy reserves to hinder the rapid de novo protein synthesis of AMO.…”
Section: Discussionsupporting
confidence: 64%
“…Thus its use to measure one process will also inhibit the other, and when one depends on the other (as is the case when denitrification depends upon nitrification for NO 3 À ), both rates are affected and the independent measurement of one is not possible. It is reported that the length of exposure to acetylene can be optimized to differentiate between its affects on nitrification and denitrification (Kester et al, 1996). N-serve is a commercial preparation that specifically inhibits NH 3 -oxidizing bacteria (Goring, 1962) and it serves as the basis for the sensitive 14 CO 2 method for measurement of nitrification rates.…”
Section: Changes In Din Concentration and Specific Inhibitorsmentioning
confidence: 99%
“…Laboratory experiments suggest that the role of AOB in NO and N 2 O production is small, but this has yet to be demonstrated in situ. Thus, although methods have been proposed to distinguish between the various sources of these gases, such as denitrifiers (87), it is unknown to what extent AOB contribute to the global production of these gases. However, it is now known that production of N 2 O under suboptimal aeration varies drastically between AOB species (83), providing further urgency to the understanding of the factors regulating population size and structure of environmental AOB.…”
Section: Problems Associated With Nitrification and Ammonia-oxidizingmentioning
confidence: 99%